Reporting of symptoms in randomized controlled trials of atopic eczema treatments: a systematic review. (1st October 2016) - Gerbens, L.A.A.; Chalmers, J.R.; Rogers, N.K.; Nankervis, H.; Spuls, P.I.; ,
Summary: 'Symptoms' is a core outcome domain for atopic eczema (AE) trials, agreed by consensus as part of the Harmonising Outcome Measures for Eczema (HOME) initiative. To standardize and validate the core domain symptoms and symptom instruments for AE trials the HOME roadmap is followed. Its first step is to establish if and how symptoms have been measured in published AE treatment trials. Therefore the Global Resource for Eczema Trials database was used to collect all randomized controlled trials (RCTs) of treatments for AE between January 2000 and April 2014. Study selection and data extraction were performed by three reviewers independently. We identified the use of symptoms in 295 of 378 trials (78%). Symptoms as a primary end point were applied by 147 RCTs (50%). Seventeen different symptoms were measured, but mostly itch and sleep loss. Symptoms were assessed by only 37% of trials by a stand‐alone symptom measurement. Overall 63% of RCTs used a composite instrument, and 30 different instruments were identified. The Scoring Atopic Dermatitis (SCORAD) index was the most commonly applied, but only 23% of RCTs reported the SCORAD symptom score separately. This systematic review demonstrates that symptoms, most frequently itch and sleep loss, are commonly reported in AE treatment trials, but are measured using many different instruments. Often symptoms are evaluated as part of a composite instrument, and currently it is not possible to extract symptoms‐only data from most published studies. Future trials should report symptom scores to permit meta‐analysis of the core outcomes.